Organizational auditing and assurance in the digital age - Marques, Rui Pedro Figueiredo; Santos, Carlos, 1953-; Inacio, Helena, 1966- (IGI Global, 2019)
"This book discusses at an international level the challenges and developments in the auditing field to ensure the auditing quality despite the continuous changes on IT and market requirements (supervisors, shareholders, stakeholders, among others). It also fills a gap in the areas related to information systems auditing and continuous assurance on businesses processes"--